Determination of individual stability constants of coexisting molecular complexes formed by unresolvable isomers. Issue 2 (1st February 2019) - Inoue, Motomichi; Virués, Claudia; Higuera-Ciapara, Inocencio
ABSTRACT: Some biogenic substances undergo steric isomerism or tautomerism in which the isomers are unresolvable. Naturally, the isomers are expected to form molecular complexes with distinct stabilities. This paper proposes the method of determining individually the stability constants of complexes formed under isomerisation and complexation equilibria: the NMR titration curves are modelled and formulated for fast and slow isomeric equilibria, the process of least-squares fittings is explained, and the application to supramolecular complexation of unresolvable isomers is discussed as compared with NMR titration data reported for α- and β-D-glucosamine anomers. Graphical Abstract: